DEVELOPING SKILLS TO IMITATE SHAPES USING PROJECT BASED LEARNING MODELS, EXPLICIT INSTRUCTION, AND FLANNEL MEDIA IN THE B1 GROUP OF BAKTI 1 ISLAMIC KINDERGARTEN BANJARMASIN - Khalifah, Lutpia; Permatasari, Nina (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2024)
The purpose of the study is to describe teacher activities, children's skills, and children's developmental outcomes in imitating shapes. This research approach uses qualitative with the type of classroom action research, carried out in 4 meetings, the research setting is on the B1 group of children of Bakti 1 Islamic Kindergarten Banjarmasin which amounted to 14 children (9 boys and 5 girls). The data collection technique uses observation. The results of the study showed that (1) the teacher's activity at the 1st meeting received a score of 20 in the